2006
DOI: 10.1097/00000542-200612000-00015
|View full text |Cite
|
Sign up to set email alerts
|

A Multicenter Clinical Study of the Safety and Activity of Maleimide-Polyethylene Glycol–modified Hemoglobin (Hemospan®) in Patients Undergoing Major Orthopedic Surgery

Abstract: In comparison with Ringer's acetate, Hemospan mildly elevates hepatic enzymes and lipase and is associated with less hypotension and more bradycardic events. The absence of a high frequency of serious adverse events suggests that further clinical trials should be undertaken.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(65 citation statements)
references
References 22 publications
3
61
0
Order By: Relevance
“…The half-life of the PEG-Hb moiety is approximately 20 hours in rats and humans. 27 Comparison of MP4CO and MP4OX in both the NY1DD and the HbAS mice allows clear distinction of CO gas from the solution properties of PEG-Hb, which includes effects on plasma volume and peripheral perfusion demonstrated previously with MP4OX. 28 The bioavailability of CO from MP4CO is demonstrated in the current study by the elevated concentration of CO in expired air from sickle mice treated with MP4CO, but not with MP4OX.…”
Section: Discussionmentioning
confidence: 92%
“…The half-life of the PEG-Hb moiety is approximately 20 hours in rats and humans. 27 Comparison of MP4CO and MP4OX in both the NY1DD and the HbAS mice allows clear distinction of CO gas from the solution properties of PEG-Hb, which includes effects on plasma volume and peripheral perfusion demonstrated previously with MP4OX. 28 The bioavailability of CO from MP4CO is demonstrated in the current study by the elevated concentration of CO in expired air from sickle mice treated with MP4CO, but not with MP4OX.…”
Section: Discussionmentioning
confidence: 92%
“…A recent phase II multicenter randomized prospective safety study on 90 elderly patients undergoing elective hip arthroplasty has confirmed these observations. MP4 had no serious adverse effects; the mild elevation of amylase, lipase and liver enzyme was not statistically significant but there were a trend to more bradycardia events in the MP4 group [119]. However, there is no information about preoperative medical treatment, particularly β-blockers.…”
Section: Hemospan)mentioning
confidence: 93%
“…1) formed by linking one Hb molecule to soluble polymers. A maleimidepolyethylene glycol conjugated Hb was developed for clinical trial (Olofsson et al 2006;Winslow 2006).…”
Section: First-generation Oxygen Carriersmentioning
confidence: 99%